Logistics Process of Last Mile Package Delivery Facilities : Proses Logistik Sarana Angkut Pengiriman Paket Last Mile - Suhada, Agus Karya; Joyodiharjo, Bismo Jelantik; Sulistyaningtyas, Tri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Online markets in Indonesia which provide easy services for traders and buyers, in carrying out community economic activities. The pandemic condition (stay at home) has also triggered the rise of the online market so that post-pandemic it encourages changes in consumer lifestyle patterns in society and increase the expedition service businesses for the delivery of goods and food packages, especially in final delivery activities (last mile) which are directly for the purpose of servicing recipient consumers. Highlighting motorbike vehicles which are widely used for goods delivery expeditions, these are not specifically designed as a means of transporting goods, so the goods carried are very at risk of being damaged by falls and rainy weather which often hampers performance as a courier. The aim of this activity is identify goods transportation facilities are needed for courier officers (last mile) to meet the criteria for the expedition designation category who can deliver goods to the front of the house according to the customer's expectations. This activity uses design thinking and interview methods. This activity focuses on analyzing the feasibility and effectiveness as a means of supporting the delivery of online service packages by courier workers, using two-wheeled motorbikes. This activity shows the current problem of the courier officers (last mile) that use their private motorbikes, even though these motorbikes are not specifically designed as a means of transporting goods. Meanwhile, the needs and opportunities for working as a courier require that you still be able to carry out your expeditions, using existing facilities, namely a sack as a container for storing luggage plus a strap. This gradually requires design improvements to increase professionalism in the field of last mile services. It is hoped that this activity can be used as reference material for vehicle designers, as a last mile supporting facility which is a design requirement that includes placement position, width dimensions, load capacity, and factors for goods safety and courier safety.